How do you find the inverse of f(x) = x^3 + 2x and is it a function?

1 Answer
Aug 15, 2016

f^(-1)(y) = root(3)((9y+sqrt(81y^2+96))/18) + root(3)((9y-sqrt(81y^2+96))/18)

which is a function.

Explanation:

Let y = f(x) = x^3+2x

We want to solve:

x^3+2x-y = 0

for x (i.e. treating y as a constant)

Note that x^3+2x = x(x^2+2) is strictly monotonic increasing. So there will be exactly one Real root for any Real value of y.

graph{x^3+2x [-10, 10, -5, 5]}

Use Cardano's method...

Let x = u+v. Then:

u^3+v^3+(3uv+2)(u+v)-y=0

Add the constraint v=-2/(3u) to eliminate the (u+v) term.

Then our equation becomes:

u^3-8/(27u^3)-y = 0

Multiply through by 27u^3 and rearrange slightly to get:

27(u^3)^2-27y(u^3)-8 = 0

Using the quadratic formula, we get:

u^3 = (27y+-sqrt((-27y)^2-4(27)(-8)))/(2*27)

=(27y+-sqrt(729y^2+864))/54

=(27y+-3sqrt(81y^2+96))/54

=(9y+-sqrt(81y^2+96))/18

Since these roots are Real and the derivation is symmetric in u and v, we can use one of these roots for u^3 and the other for v^3 to find the Real root of the cubic:

x = root(3)((9y+sqrt(81y^2+96))/18) + root(3)((9y-sqrt(81y^2+96))/18)

The other two roots are non-Real complex roots and need not concern us.

This Real zero gives us an inverse function for the original cubic function f(x)

f^(-1)(y) = root(3)((9y+sqrt(81y^2+96))/18) + root(3)((9y-sqrt(81y^2+96))/18)